2016
DOI: 10.1371/journal.pone.0165986
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Functional Advantages of Knots in Proteins

Abstract: We analysed the structure of deeply knotted proteins representing three unrelated families of knotted proteins. We looked at the correlation between positions of knotted cores in these proteins and such local structural characteristics as the number of intra-chain contacts, structural stability and solvent accessibility. We observed that the knotted cores and especially their borders showed strong enrichment in the number of contacts. These regions showed also increased thermal stability, whereas their solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 38 publications
0
73
0
Order By: Relevance
“…It has been proposed that knotted proteins have enhanced thermal (20,26), mechanical (26,27,128) and structural (127) stabilities. Another possibility is that knots help shape and stabilize the active site of enzyme (129)(130)(131), and in some cases it has even been suggested that knots can control enzymatic (130) and signaling activity (132). A recent study put forward the view that knots can impair protein degradation by ATP-dependent proteases leading to partially degraded products with potentially new functions (133).…”
Section: Functional Advantages Of Knots In Proteinsmentioning
confidence: 99%
“…It has been proposed that knotted proteins have enhanced thermal (20,26), mechanical (26,27,128) and structural (127) stabilities. Another possibility is that knots help shape and stabilize the active site of enzyme (129)(130)(131), and in some cases it has even been suggested that knots can control enzymatic (130) and signaling activity (132). A recent study put forward the view that knots can impair protein degradation by ATP-dependent proteases leading to partially degraded products with potentially new functions (133).…”
Section: Functional Advantages Of Knots In Proteinsmentioning
confidence: 99%
“…The main differences are mostly located at the RBDs (Figure 1a indicating that it does untangle during prepore-to-pore transition ( Figure 3b). A 31 trefoil protein knot is the most simple and common knot type 18 . It mostly occurs in smaller proteins or enzymes such as methyltransferases and carbonic anhydrases 19 .…”
Section: Differences In the Shell Domainmentioning
confidence: 99%
“…With ~280 kDa (mass of Pl-TcdA1 monomer), TcA is, to our knowledge, by far the largest protein for which such a knot has been observed. The folding mechanism of a knotted protein has been shown to be quite complex and the folding rate of knotted proteins is decreased 18,20 . These findings suggest that it is rather surprising that the complex TcA structure contains a knot.…”
Section: Differences In the Shell Domainmentioning
confidence: 99%
“…[7][8][9] Several studies have highlighted the importance of naturallyo ccurring molecular knots. [10,11] Similarly,t he formation of knots in polymers is thought to result in unique thermal, mechanical and dynamical properties. [10,11] Similarly,t he formation of knots in polymers is thought to result in unique thermal, mechanical and dynamical properties.…”
Section: Introductionmentioning
confidence: 99%